Komunikasi Persuasif Ibu Kepada Anak dalam Menanamkan Perilaku Ibadah Sholat: Studi Kasus Desa Tonjong Kecamatan Tajurhalang Kabupaten Bogor - Adawiyah, Arobiatul; Fahmi Irfani; Yono (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The people of Tonjong Village, Tajurhalang District, Bogor Regency, the majority of whom are Muslim and are active in religious activities, including the routine monthly recitation of mothers, as well as teenagers and fathers who pray five times a day at the mosque. Not only parents but also children are taught to worship from a young age by their parents. Therefore, researchers are interested in knowing how mothers' persuasive communication is carried out with their children in instilling prayer behavior. The objectives of this research are: 1) To find out how persuasive communication is carried out by mothers with children in instilling prayer behavior in Tonjong Village, Tajurhalang District. 2) To find out the persuasive communication model used by mothers with their children in instilling prayer behavior. This research uses a qualitative approach by conducting observations, interviews and documentation regarding Persuasive Communication from Mothers to Children in Instilling Prayer Behavior. The results of this research show that; (1) It is concluded that the persuasive communication carried out by mothers with their children in instilling prayer behavior uses several methods, namely: advice method, habituation method, example method, taghrib method and tarhib method. (2) The model used by parents to use persuasive communication between mothers and children in instilling prayer behavior in Tonjong village is the Aristotelian model, which emphasizes three important elements, namely the speaker, message and listener.